Ring-fencing digital corporations: Investor reaction to the European Commission's digital tax proposals - Daniel Klein; Christopher A. Ludwig; Christoph Spengel (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
We study the effect of digital tax measures on firm value. By employing an event study methodology, we analyze investor reaction to the European Commission's proposals on the taxation of digital corporations. Examining the stock returns of potentially affected corporations surrounding the draft directives' release, we find a significant abnormal capital market reaction of -0.692 percentage points. The investor reaction is more pronounced for firms that engage more actively in tax avoidance, have a higher profit shifting potential, and for those with higher exposure to the EU. The market value of digital and innovative corporations decreased by at least 52 billion euro in excess of the regular market movement during the event window. Overall, our study reveals that expectations about ringfencing digital tax measures impact firm values.
Keywords: H25; H26; K34; G14; 330; digital taxation; corporate tax; digital economy; event study